2014
DOI: 10.1007/s10853-014-8067-9
|View full text |Cite
|
Sign up to set email alerts
|

Reverse phase transformation of martensite to austenite in stainless steels: a 3D phase-field study

Abstract: The martensitic transformation of austenite as well as the reversion of martensite to austenite have been reported to significantly improve mechanical properties of steels. In the present work, three dimensional (3D) elastoplastic phasefield simulations are performed to study the kinetics of martensite reversion in stainless steels at different annealing temperatures. The input simulation data is acquired from different sources, such as CALPHAD, ab initio calculations and experiments. The results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…Since the lath boundaries are the areas where a small driving force is sufficient to overcome the transformation barriers, reversion occurs primarily at the lath boundaries. These results are in good agreement with our study on reversion of martensite to austenite in stainless steels [28].…”
Section: Microstructure Evolution During Pressure Releasesupporting
confidence: 93%
See 1 more Smart Citation
“…Since the lath boundaries are the areas where a small driving force is sufficient to overcome the transformation barriers, reversion occurs primarily at the lath boundaries. These results are in good agreement with our study on reversion of martensite to austenite in stainless steels [28].…”
Section: Microstructure Evolution During Pressure Releasesupporting
confidence: 93%
“…In the case of steels, where martensitic transformation and reversion are associated with significant amount of plastic deformation of the material, we observed that a large amount of plastic strains are retained after the reverse phase transformation [28]. The amount of plastic deformation in Zr is not as large as that in steels.…”
Section: Microstructure Evolution During Pressure Releasementioning
confidence: 64%
“…Reliable thermodynamic databases are essential tools in the design of AHSS. [58][59][60][61][62][63][64] They need to cover a number of alloying (Mn, Al, Cr, Ni, Si, C, N, B) and tramp elements (Zn, Cu, H, P, S), doped on purpose or entering through ores and scraps. Each of these elements contributes differently to the stability of the iron-rich solutions (liquid, ferrite, austenite (c), and epsilon (e)) and the second-phase precipitates.…”
Section: A Key Thermodynamic Concepts For Advanced High-strength Stementioning
confidence: 99%
“…But the strain hardening effect becomes complex and is temperature-related: at low temperature (<600 • C), the strain hardening effect is not significant; but at the temperature of 900 • C, the flow stress increases linearly with the plastic strain, and the strain hardening effect becomes significant. This phenomenon is considered to be related with the phase transition, when the temperature reaches and exceeds the critical phase transition temperature, some tempered martensite grains in the metal gradually transforms into austenite grains [19,20], resulting in the decrease of strength but the increase of plasticity.…”
Section: Plastic Constitutive Model Fittingmentioning
confidence: 99%